IMPLEMENTATION OF ISLAMIC VALUES IN DEMOCRACY: EXAMINING THE POLICIES OF PARTAI KEADILAN SEJAHTERA ON CONTEMPORARY ISSUES - Alwalid Assyauqi; Aminuddin (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Indonesia’s post-Reformasi democratic transition has created broader political opportunities for parties representing diverse ideological orientations, including those grounded in Islamic values. Within this context, Partai Keadilan Sejahtera (PKS) has positioned itself as an Islamic-based political party that seeks to integrate Islamic principles within Indonesia’s constitutional democratic framework. This study aims to examine how Partai Keadilan Sejahtera responds to contemporary socio-political issues through its political positions and policy orientations, particularly in relation to social justice, public welfare, governance, and pluralism in a democratic society. This research employed a qualitative approach using a library research method. Data were collected from official party documents, including policy platforms and political manifestos, as well as relevant scholarly books and journal articles. The data were analyzed descriptively and analytically to explore the relationship between Islamic values as the ideological foundation of Partai Keadilan Sejahtera and the party’s political practices. The findings indicate that Partai Keadilan Sejahtera seeks to operationalize Islamic principles, such as justice, integrity, and consultation (shūrā), within contemporary democratic institutions and political processes. Nevertheless, the implementation of these values is frequently shaped by political pragmatism and the dynamics of electoral competition. This study concludes that Partai Keadilan Sejahtera represents a contextual, adaptive, and pragmatic model of Islamic political engagement within Indonesia’s democratic system.